Home » If g(x) = x2 + 3x + 4, find g(x + 1) – g(x)

If g(x) = x2 + 3x + 4, find g(x + 1) – g(x)

If g(x) = x2 + 3x + 4, find g(x + 1) – g(x)
  • A.
    (x + 2)
  • B.
    2(x + 2)
  • C.
    (2x + 1)
  • D.
    (x2 + 4)
Correct Answer: Option B
Explanation

g(x) = x2 + 3x + 4
= g(x + 1) = (x + 1)^2 + 3(x + 1) + 4
= x2 + 1 + 2x + 3x + 3 + 4
= x2 + 5x + 8
g(x + 1) – g(x) = x2 + 5x + 8 – (x2 + 3x + 4)
= x2 + 5x + 8 – x2 + 3x + 4
= 2x + 4
= 2(x + 2)

Related:  Simplify (frac{4frac{3}{4} - 6frac{1}{4}}{4frac{1}{5} text{ of } 1frac{1}{4}})